KNOWLEDGE AND PRACTICE REGARDING EXCLUSIVE BREASTFEEDING DURING THE FIRST 6 MONTHS AMONG MOTHERS OF INFANTS UNDER 6 MONTHS IN CA MAU CITY, CA MAU PROVINCE IN 2025 (Vietnam Journal of Community Medicine, 2026)
Objectives: To determine the prevalence of adequate knowledge and correct practices regarding exclusive breastfeeding during the first six months and to identify associated factors among mothers in Ca Mau city, Ca Mau province.Methods: A cross-sectional descriptive study was conducted among 390 mothers with infants under six months of age in Ca Mau city. Knowledge and practices concerning exclusive breastfeeding were assessed using a structured questionnaire. Mothers were classified as having adequate knowledge or correct practice if they achieved a score of ≥ 80% of the total points.Results: The rate of mothers with adequate knowledge of exclusive breastfeeding was 60.26%, while the rate of correct practice was 68.97%. Factors significantly associated with adequate knowledge included an educational level of high school or higher (OR = 1.59), employment as a civil servant/public official (OR = 2.95), autonomy in infant feeding decisions (OR = 2.81), and receiving counseling from healthcare workers (OR = 3.08). Correct practice was significantly associated with maternal age ≥ 35 (OR = 2.33), educational level ≥ high school (OR = 2.08), vaginal delivery (OR = 2.17), multiparity (OR = 3.30), and adequate knowledge (OR = 17.11).Conclusion: The prevalence of adequate knowledge and correct practice regarding exclusive breastfeeding remains suboptimal. It is essential to strengthen health communication and education, particularly through healthcare professionals, to enhance knowledge and improve exclusive breastfeeding practices within the community.
Keywords: Exclusive breastfeeding, knowledge, practice, associated factors, mothers, Ca Mau.